Promosi Gizi dan Kesehatan bagi Wanita Hamil, Wanita Menyusui, dan Ibu Balita dalam Rangka Pencegahan Stunting di Kabupaten Lampung Tengah, Lampung - Sutarto Sutarto; Asep Sukohar; Ratna Dewi Puspita Sari; Winda Trijayanthi; Sofyan Musabiq Wijaya (Jurnal Pengabdian Pada Masyarakat, 2021)
PROMOTION OF NUTRITION AND HEALTH FOR PREGNANT WOMEN, BREASTFEEDING WOMEN, AND MOTHERS TODDLER IN THE CONTEXT OF STUNTING PREVENTION IN LAMPUNG TENGAH REGENCY, LAMPUNG. One of the determining factors for the success of health development is nutritional status. Health promotion efforts to increase awareness, willingness and ability of both individuals, families, groups and communities to live healthy and it is necessary to increase nutrition and health promotion for pregnant women and mothers under five. This activity was carried out in the context of preventing stunting in Tanggamus and Tanggamus Regencies which was carried out by the Service Team of the Faculty of Medicine, University of Lampung. Various health promotion efforts have been made to obtain optimal results through nutrition and health promotion. This activity aims to assist in the success of national health development through improving nutritional status, through increasing public knowledge about clean and healthy living habits in household settings, a balanced nutrition menu in preventing the incidence of stunting in the family. The methods used in carrying out this activity are lectures, focus group discussions, counseling on the portion of my plate, skill practice and food serving competitions for lokal products to improve nutrition for pregnant women and toddlers. Results of nutrition and health promotion activities for pregnant women and mothers under five in the context of preventing stunting in Central Lampung and Tanggamus districts. can assist in the success of national health development through improving nutritional status.